Regional bone density patterns of the tibial plateau: implications for finite element analysis - Besa, Pablo; Alegría, Anselmo; González, Nicolás; Biancardi, Fiorella; Vidal, Catalina; Cikutovic, Pablo; Andia, Marcelo E.; Mura, Joaquín (Frontiers in Bioengineering and Biotechnology, 2025)
The tibial plateau has different anatomical regions and heterogeneous bone densities. Most finite element simulation (FEM) studies of tibial plateau fracture fail to account these regional variations, which may significantly influence biomechanical behavior. This study aimed to quantify the regional density profile of the tibial plateau using Hounsfield Units (HU) from computed tomography (CT) scans and explore associations between density, age, and sex. We developed a novel measurement protocol to compare HU values of the subchondral bone and cancellous bone in eight different regions of the tibial plateau. Results demonstrated that patient age and female sex were associated with reduced bone density. Subchondral bone and medial bone had significantly higher density than metaphyseal and lateral bone, respectively. This findings could have implications on orthopedic modeling of tibial plateau fractures using FEM. Current FEM should consider distinct regions in tibial plateau to improve accuracy. Conclusion: Tibial plateau heterogenous bone density distribution could contribute to explain the low predictive accuracy in FEM models.